Integrating agrifood system strategies with climate change policies and commitments in Tajikistan - Babu, Suresh Chandra; Tohirzoda, Sino; Akramov, Kamiljon T.; Srivastava, Nandita; Aliev, Jovidon (International Food Policy Research Institute, 2024)
The Declaration on Sustainable Agriculture, Resilient Food Systems, and Climate Action endorsed by over 150 countries at UNFCCC-COP28 highlights global recognition of the unprecedented adverse climate impacts on food systems resilience and the need to expedite the integration of agriculture and food systems into climate action. While integration is necessary to ensure favorable sectoral level climate action outcomes, there are currently no concrete frameworks and case studies showcasing how to support this integration process at the country level.